SKABELSEN AF DET MODERNE SUBJEKT: Magt og subjektivitet hos Weber, Elias og Foucault - Villadsen, Kaspar (Tidsskriftet Antropologi, 2007)
This article discusses the emergence of the modern subject by examining the work of Max Weber, Nobert Elias and Michel Foucault. It argues that their work each make key contributions to the genealogy of the modern subject, using a similar approach to history and sharing a similar focus and power in social life. Yet, there are also important differences that should be acknowledged when trying to unify the three criticial thinkers.